Evaluation of hydroxamate-based resins towards a more clinically viable 44Ti/44Sc radionuclide generator. (February 2023) - Gajecki, Leah; Marino, Celine M.; Cutler, Cathy S.; Sanders, Vanessa A.
Abstract: Several hydroxamate-based resins were synthesized and tested for use in 44 Ti/ 44 Sc generator systems in small scale experiments (740 kBq 44 Ti). The most promising resin was tested further in larger scale generator studies (37 MBq). This resin displayed impressive retention of 44 Ti over several elutions, and high quantities of 44 Sc were obtained in small volumes of dilute HCl eluents. Initial radiolabeling experiments were conducted and demonstrated the possibility of direct radiolabeling of the generator produced 44 Sc with DOTA. Highlights: Novel hydroxamate resin for use in 44 Ti/ 44 Sc radionuclide generator. Clinically viable generator system. Direct radiolabeling.